Practical tunnelling ... sub-excavating, timbering and the construction of the brickwork of tunnels ... - Simms, Frederick Walter, 1803-1865 (Crosby Lockwood, 1877)
This title explains in detail the setting out of the works, shaft sinking, and heading driving, ranging the lines, and levelling under ground, sub-excavating, timbering and brickwork construction of tunnels, with additional chapters relating to the St Gothard and Mont Cenis tunnels.